Illustrated medical pharmacology - Kapoor, A. K. (Professor of pharmacology); Raju, S. M. (Jaypee Brothers Medical Publishers (P) Ltd., 2013)
Comprehensive guide to medical pharmacology for undergraduate students. Each chapter features review questions for self assessment.